Pemberdayaan ibu dengan edukasi literasi digital sebagai strategi mediasi orangtua dalam mengontrol penggunaan gadget pada anak usia sekolah - Sarini Sarini; Dewi Rubi Fitriyani; Dayana Noprida; Komalasari Komalasari (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: The rapid advancement of digital technology has made gadgets an integral part of the lives of primary school-aged children. While gadgets offer educational benefits, uncontrolled use can potentially lead to negative impacts on children's physical, psychological, social, and behavioral well-being. Mothers, as primary caregivers, play a crucial role in supervising and mediating their children's gadget usage. Purpose: To enhance mothers' digital literacy regarding the supervision of children's gadget use through an e-module-based parental mediation strategy. Method: The activity was conducted on July 5, 2026, at the Puri Calisya Indah Housing Complex (Block C3, RT 43, Cibalado Hamlet, Gintungkerta, Klari, Karawang). The target audience consisted of mothers with primary school-aged children (6–12 years old), with a total of 25 participants. The primary educational materials used were a digital literacy e-module and leaflets. Pre-test and post-test data were analyzed descriptively by comparing the average scores before and after the intervention. The increase in scores served as an indicator of the community service activity's success in improving participants' knowledge and understanding regarding the supervision of children's gadget use. Results: The findings indicate that prior to the educational activity, 32.0% of respondents fell into the